Acceleration-speed profiles in LaLiga: the influence of initial running speed and differences between positional roles in elite football players - Garrosa, Fabio; Saiz, Javier Mallo; Quintero-Illera, José Luis; Rubio-López, Jorge; López-Del Campo, Roberto; Jiménez-Rubio, Sergio (Biology of Sport, 2025)
The aim of this study was to examine the accelerations carried out by professional football players during an elite standard competition in relation to the initial running speed. An additional purpose was to determine the acceleration-speed (AS 0 ) profile of the players in relation to the position in the team formation. Methods: A total of 8426 match observations from 363 players, categorized into six positional roles, who took part in the Spanish First Division (LaLiga) were examined with a semi-automatic multiple-camera video system during three consecutive seasons (from 2020–21 to 2022–23). The value of every acceleration performed during the games was related to its initial running speed, and the individual maximal and mean AS 0 profiles of all the players were calculated using linear regression models. Results: A strong inverse relationship was detected between the acceleration values and the initial running speed for both the MaxAS 0 and the MeanAS 0 profiles ( r = -0.990; p < 0.001 and r = 0.946; p < 0.001, respectively). This trend was consistent across all playing positions, with forwards exhibiting the greatest acceleration capacity and central defenders the smallest. There were differences ( p < 0.05–0.001) in the slope of the AS 0 profile between playing positions. Conclusions: This study shows that traditional fixed acceleration thresholds might overestimate high-intensity efforts that begin at low movement speeds and underestimate those that start at higher speeds. Thus, AS 0 profiles can provide a valuable tool to monitor physical match performance more objectively and help to discriminate the acceleration capacity between playing positions.